Assessing the Natura 2000 network with a common breeding birds survey. (7th February 2013) - Pellissier, V.; Touroult, J.; Julliard, R.; Siblet, J. P.; Jiguet, F.
Abstract: Natura 2000 (N2000) is a network of European sites focused on the conservation of specific species and habitats. Despite the known importance of common biodiversity in ecosystem functioning, common species are currently not explicitly targeted by conservation initiatives in France. In this study, we investigated whether the N2000 network contributes to the protection of common breeding bird species. In particular, we focused on species abundance and species specialization, community specialization and community trophic levels. We also determined the effects of N2000 on temporal trends of specialist and generalist bird groups. We studied 100 species in 1461 plots monitored by the French Breeding Bird Survey (BBS) between 2001 and 2010. We found that species abundance increased for 54 species with the proportion of the plot covered by N2000 areas in the plot. The bird species with the abundances that were most influenced by proportion of the plot covered by N2000 areas were predominantly habitat specialists. Bird communities inside N2000 sites were more specialized and exhibited higher trophic indices than communities outside N2000 sites. We found no differences in the temporal trends of farmland and woodland birds inside and outside N2000 sites, but the temporal trend of generalist species was positive outside N2000 sites and stable inside. We concluded that N2000 sites showed greater abundance of a majority of common bird species but that the network was established too recently to assess its influence on population trends. The French BBS has proved to be an efficient tool in assessing protected area networks.